Characterization of Didymellaceae leaf spot associated with Elymus plants in the Tibetan Plateau of China - Liu, Jiaqi (Plant disease, 2025)
Elymus plant is a dominant herbage in the Tibetan Plateau of China. Leaf spot disease restricts the production and utilization of Elymus spp., yet comprehensive studies on the etiology, and epidemiology of this disease in Elymus plants remain notably limited. In this study, a two-year investigation (2021 to 2022) was conducted on Elymus plants across both natural and cultivated grasslands of Gansu, Qinghai, and Sichuan Province in the Tibetan Plateau of China. The results demonstrated that leaf spot disease is a prevalent disease, with particular severity occurring at the heading stage of growth. A total of 184 strains, representing 25% of all initially isolated strains, were attributed to the Didymellaceae family (comprising Didymella, Leptosphaerulina, and Neoascochyta) based on the identity of their ITS sequences in NCBI and the similarity of cultural characters, which suggested that Didymellaceae leaf spot (DLS) is likely to be one of the most predominant foliar diseases affecting Elymus plants. Fifteen representative cultures were selected for further study based on morphology, symptomatology, and the isolation rates. Multi-locus phylogenetic analysis (ITS, LSU, RPB2, and TUB2) coupled with morphological features showed that these isolates were finally identified as five new record species, including D. boeremae, D. pomorum, L. miscanthi, N. cylindrispora, and N. europaea. Pathogenicity analysis showed that the virulence of these five species varied on both E. nutans and E. sibiricus plants, of which N. cylindrispora and N. europaea was more aggressive. Coupling with natural and artificially inoculated symptoms, three typical symptoms of DLS on Elymus plants were specified in this study, i.e., small dark brown spots (D. boeremae and D. pomorum), white and linear spots with black margins (L. miscanthi), and dark brown spots with a yellow halo (N. cylindrispora and N. europaea). Overall, these findings will help us comprehend the diversity of the family Didymellaceae in Elymus spp. and provide a basis for diagnosis in the field and future management of leaf spot disease (especially for DLS) on Elymus plants